Direct growth of nickel cobalt layered double hydroxide on nickel foam via redox reaction between nitrate ion and ethanol for hybrid supercapacitors. (20th January 2021) - Nguyen, Thi Toan; Mohapatra, Debananda; Kumar, Deivasigamani Ranjith; Baynosa, Marjorie; Sahoo, Sumanta; Lee, Jintae; Shim, Jae-Jin
Highlights: Ni/Co-LDHs were formed through the redox reaction of NO3 ¯ and C2 H5 OH. Remarkable specific capacity of 1757 c g –1 (4392 f g –1 ) was obtained at 1 mA cm −2 . Diffusion-controlled faradaic process contributed 90% in the charge storage. Ni/Co-LDHs//AC showed energy density 51.1 Wh kg –1 and power density 12.1 kW kg –1 . Abstract: Binary combinations of transition metal-layered double hydroxides (LDHs) have attracted considerable attention for supercapacitor applications owing to their extraordinary charge storage, low internal resistance, and superior electrochemical stability. In this study, nickel–cobalt LDH (Ni–Co LDHs) nanosheets were grown hierarchically on the surface of Ni foam (NF@Ni–Co LDHs) using a simple solvothermal approach without any binder elements. Interconnected nanosheets with a thickness of ~25 nm were grown uniformly on the nickel foam. The synergistic combination of Ni 2+ and Co 2+ /Co 3+ LDHs grown directly on nickel foam resulted in a remarkably high specific capacity of 1757 C g −1 (4392 F g −1 ) at a current density of 1 mA cm −2 (0.44 A g −1 ). Furthermore, a hybrid supercapacitor (HSC) device was fabricated using activated carbon as the anode and NF@Ni–Co LDHs as the cathode. The hybrid device exhibited high energy densities of 51.1 Wh kg −1 (at a power density of 777 W kg −1 and a current density of 1.0 A g −1 ) and 11.8 Wh kg −1 (at a power density of 12.1 kW kg −1 and current density of 20 A g −1 ). The electrochemical stability of the HSC device was 72.2% after 10, 000 charge/discharge cycles at a current density of 10 mA cm −2 . The electrochemical performance of the Ni–Co LDHs nanosheets on Ni foam in a three-electrode system and as a hybrid device highlights its potential in energy storage applications. Graphical abstract: Image, graphical abstract